Making the Law Explicit : the Normativity of Legal Argumentation. - Klatt, Matthias (Studies in international law (Stockholm, Sweden), 2008)
Legal argumentation consists in the interpretation of texts. Therefore, it has a natural connection to the philosophy of language. Central issues of this connection, however, lack a clear answer. For instance, how much freedom do judges have in applying the law? How are the literal and the purposive approaches related to one another? How can we distinguish between applying the law and making the law?. This book provides answers by means of a complex and detailed theory of literal meaning. A new legal method is introduced, namely the further development of the law. It is so far unknown in Anglo.